Library ergonomics a case study of the cataloging workstations of selected universities in the Philippines - Lacsamana, Marlon T.; Gonzales, Grace Marie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
Ergonomics is the investigation of human physical and mental abilities and the application of the knowledge in products, equipment and artificial environment (Garner 1999). The science of ergonomics can greatly improve the working conditions of the catalogers since cataloging is admittedly a strenuous, monotonous task, with catalogers spending a huge amount of time confined in a restrictive workstation. Poor ergonomics would be equivalent to human or cognitive error, where problems can both be physical or mental.
A case study conducted on the cataloging workstations of selected universities in Metro Manila showed that majority do not practice ergonomics principles. A number of catalogers form the top four universities totaling fifty two (52) respondents, were asked to answer questionnaires to get an in-depth assessment of the ergonomic practices in those cataloging departments.
Out of the twenty-seven (27) libraries, fifty-two questionnaires were sent, 52 (100 percent) responded. Of this 100 percent do not really have any ergonomic awareness among the catalogers. Providing catalogers with ergonomic awareness will make them realize that their well-being is an important key to successful and productive work outcome.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Human engineering; Microcomputer workstations